1994
DOI: 10.1148/radiology.193.2.7972739
|View full text |Cite
|
Sign up to set email alerts
|

Prostate carcinoma: assessment of diagnostic criteria for capsular penetration on endorectal coil MR images.

Abstract: Sensitivity and specificity were generally low for the diagnostic criteria. The usefulness of endorectal coil MR imaging in staging prostate cancer may be limited by the lack of diagnostic signs that uniformly identify extracapsular penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(80 citation statements)
references
References 0 publications
2
69
0
9
Order By: Relevance
“…Accuracy levels ranged from 54% to 83%. In three ofthese studies, fast spin-echo MR images with an ERC were correlated with histopathologic mapping [12,14,16]. As an adjunct to staging, the volume of prostate cancer is also important for prognosis [17-1 9].…”
Section: Objectivementioning
confidence: 99%
“…Accuracy levels ranged from 54% to 83%. In three ofthese studies, fast spin-echo MR images with an ERC were correlated with histopathologic mapping [12,14,16]. As an adjunct to staging, the volume of prostate cancer is also important for prognosis [17-1 9].…”
Section: Objectivementioning
confidence: 99%
“…26 In fact, previous studies have shown that if a diagnosis of extraprostatic tumour spread is based solely on obvious findings, the high specificity may be associated with a downside of extremely poor sensitivity. 27 When stricter definitions were used, accuracy rates fell from an average sensitivity of 70%-80% to below 40% in one particular report. 28 Using contour deformity with only irregular margins as a criterion for capsular penetration, Chelsky et al 9 achieved an increase in specificity from 78% to 96%.…”
Section: Discussionmentioning
confidence: 98%
“…All operations were performed by one surgeon at one institution The criteria for capsular penetration included: low signal infiltration of the periprostatic fat on T1 images, focal bulging of the capsule adjacent to the tumour ( Fig. 1) and loss of signal within the seminal vesicles on T2-weighted images [9].…”
Section: Methodsmentioning
confidence: 99%